(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
IMPRESCRIPBILITY OF PERSONALITY RIGHTS AS A WAY OF PROTECTING THE DIGNITY OF HUMAN PERSON ABSTRACT The rights of personality, inherent in the dignity of the human person, are inviolable, lifelong and imprescriptible, apply to every human person who acquired them from birth. Although personality rights are lifelong, that is, they persist as long as there is life, they are also safeguarded after the death of the human person. Because of their importance, the rights of personality not traded, and so little alienable. Although the Civil Code of 1916 completely ignored the rights of personality, given that due to its patrimonialist nature the legislator understood that it did not deserve to be covered, however, the Federative Constitution of Brazil of 1988 clearly guaranteed them and, Civil Code of 2002, filled the gap left by the Civil Code of 1916, devoting, in its general part, a chapter to deal with the rights of the personality, thus guaranteeing the right to the dignity that each and every human person holds. Keywords: Right of personality. Imprescriptibility. Human dignity.